Votingbehavior as Political Participation: The Role of Trust Inpolitical Candidate and Personal Affect - Sa'id, Mochammad; Prasetyo, Vonny Anggraeni; Chusniyah, Tutut; Noorrizki, Rakhmaditya Dewi (Universitas Muhammadiyah Surakarta, 2019)
Purpose:This study aims to investigate the role of trust in political candidate and personal affect on voting behavior.Methodology: The population of this research is permanent voters in Sukun Subdistrict, Malang City. While the study sample amounted to 100 respondents with accidental sampling technique. This study uses 3 scales as research instruments: the scale of trust in presidential candidate, the PANAS scale (The Positive and Negative Affect Schedule), and the scale of voting behavior. The research data were then analyzed using the multiple regression analysis technique.Results: The results showed that the variable of trust in candidate and personal affect jointly influenced voting behavior (F=61.676; p<0.05). The effective contribution made by the two predictor variables (trust in candidate and personal affect) to the criterion variable (voting behavior) was 56 percent. Based on this analysis, it can be concluded that the research hypothesis is accepted. The analysis also showed that the variable of trust in candidate (β=0.455) is stronger than personal affect (β=0.388) in predicting voting behavior.